Exploring principals’ roles in improving literacy in the foundation phase - Jordaan, Mache (University of the Free State, 2021)
This dissertation explored the role of the principal in improving literacy in the foundation phase. The challenges teachers and principals experienced were shown in the study as well as additional influential factors affecting literacy. This study is grounded in a theoretical framework with a focus on instructional leadership. This study comprised a qualitative research method, and the study took place in five different schools in the Motheo District, Bloemfontein, Free State, South Africa. Data were collected using individual interviews with five principals and 6 Departmental Heads. In addition, focus group interviews were conducted with 16 foundation phase teachers. Furthermore, a documentary analysis was done in each school as well. Various themes emerged from the qualitative research, and the primary focus was on the role of the principal in improving literacy in the foundation phase. The findings revealed that principals need to better understand literacy and the curriculum in the foundation phase and that literacy instruction needs urgent attention to improve learner achievement.
Dissertation (M.Ed. (School of Education Studies))--University of the Free State, 2021
Keywords: Literacy; Curriculum; Principals; Professional development; Instructional leadership; Distributor leadership